The Effect of Competitive Intensity, Organizational Slack, Entrepreneurial Orientation and Knowledge Management on Organizational Performance Mediated by Innovation in Culinary MSMEs in the Depok Region - Ari Sulistyowati; Farida Jasfar; Willy Arafah; Justine Tanuwijaya (Dinasti International Journal of Management Science, 2023)
The purpose of this study is to measure the business performance of culinary MSMEs in the Depok city area which is influenced either directly or indirectly by several variables, namely competitive intensity, organizational slack, entrepreneurial orientation, knowledge management, and innovation. This study uses data analysis techniques with multivariate analysis to test descriptive statistics and differential statistics to test hypotheses. The analytical tool used in processing data uses SEM (Structural Equation Model) based on PLS (Partial Least Square). Sampling in this study was 231 culinary MSMEs in the Depok area using the purposive sampling method. Based on the results of this study, the relationship between variables both directly and indirectly has a positive influence. The limitations in this study only discuss several RBV variables related to the internal performance of MSME business actors whereas the variables discussed emphasize the performance system of MSME actors in carrying out their business processes. The results of this study provide findings of several things that are taken into consideration for MSME business actors to improve their performance by paying attention to several indicators in each variable studied to become a reference in developing the performance of MSME business actors. This study presents several RBV variable tests to see the relationship and influence both directly and indirectly. Where previous research was not entirely in examining RBV variables